COMPARATIVE STUDY ON SOURCES OF GROWTH IN AGRICULTURE OF BANGLADESH UNDER VARIOUS SOCIO-POLITICAL REGIMES FROM 1961-2016 USING GROWTH ACCOUNTING FRAMEWORK - Fardoush, Zannatul (PEOPLE: International Journal of Social Sciences, 2018)
Investigating the determinants of economic transformation has become an important fundamental goal of the development economics. Among the economic sectors, agriculture is considered as the highly challenging area to increase the productivity and efficiency. Yet, it remains the most wide-spread economic activities with immense implications for the economic growths in many developing and least-developed countries. This study has examined the sources of growth in the agriculture sector in Bangladesh over the last five and half decade (1961-2016) under the various socio-political regimes. TFP-based Growth accounting model is used to determine the sources. Results reveal that agricultural growth in Bangladesh has a reasonable relationship with the socio-political factors. The rate of growth was lowest during the 15 years of the military regime (1975-1990). Under all non-democratic regimes and within some closed economy the growth was mainly led by the input factors. The sustainability in growth led by TFP has come only under the proper democratic environment with liberalized trade policies.